A new species of the allodapine bee genus Braunsapis from the Central African Republic (Hymenoptera: Apidae) - Engel, Michael S. (Journal of Melittology, 2013)
A new species of the allodapine bee genus Braunsapis Michener (Allodapini: Allodapina) is described and figured from a series of females collected in the Central African Republic.  Braunsapis maxschwarzi Engel, new species, is similar to B. paradoxa (Strand) from South Africa, both species sharing the concave dorsal surface of the sixth metasomal tergum and the peculiar bifid apical projection of the sixth metasomal sternum.  The new species, however, can be distinguished by the more extensively developed yellow markings of the face, the yellow pronotal lobe, the more shoulder-like posterolateral margins of the sixth tergum [more similar in this regard to B. angolensis (Cockerell) and not greatly produced as in B. paradoxa], and the more erect and prominent dorsal setae of metasomal terga IV–VI, among other traits.